MENILAI PRAKTIK PENGAJARAN EFL SAAT INI TENTANG IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH MENENGAH - salsabila, iqzzy; sahrawi; maliqul hafis (Melekliterasi Press, 2025)
This research aims to assess English as a Foreign Language (EFL) teaching practices in the implementation of the Merdeka Curriculum and identify challenges faced by teachers in applying it at the secondary school level. The research employed a case study approach with interviews as the data collection instrument, involving one curriculum teacher and one English teacher at SMPS PGRI 1 Sungai Raya Kepulauan. The findings show that teachers have developed a basic understanding of the curriculum that allows them to apply it, although not comprehensively. Teachers adopt student-centered approaches and integrate technology in the classroom, aligning with the core principles of the Merdeka Curriculum. The main challenges identified include the lack of specific training related to curriculum implementation, difficulties integrating existing pedagogical approaches with the demands of the new curriculum, and student adaptation to new learning methods. Despite facing challenges, teachers have demonstrated resilience and adaptability in implementing the curriculum relatively effectively.